2012
DOI: 10.1159/000343906
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Clinical Association of Panton-Valentine Leukocidin-Positive <b><i>Staphylococcus aureus</i></b> Isolates: A Study from Kuwait

Abstract: Objective: This study was undertaken to determine the frequency of Panton-Valentine leukocidin (PVL)-producing Staphylococcus aureus among strains isolated in our laboratory and to study the association of PVL-positive strains with clinical disease. Materials and Methods: A total of 291 S. aureus isolates obtained from different clinical specimens from June 1, 2009, to March 31, 2010, at the Farwania Hospital Laboratory were investigated for antimicrobial susceptibility, carriage of genes for PVL, and SCCmec e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
1
12
4
Order By: Relevance
“…The study also revealed that 44.3% of the isolates carried genes for PVL. This was higher than the 14.6% PVL gene-positive MRSA reported recently in a Kuwait hospital 28 but lower than the 54.2% positive rate obtained in a Saudi Arabian hospital 15 , indicating the diversity of MRSA bearing PVL genes in the GCC countries. PVL gene-positive S. aureus have been associated with necrotic skin lesions and community-acquired necrotic pneumonia 24 .…”
Section: Discussioncontrasting
confidence: 72%
“…The study also revealed that 44.3% of the isolates carried genes for PVL. This was higher than the 14.6% PVL gene-positive MRSA reported recently in a Kuwait hospital 28 but lower than the 54.2% positive rate obtained in a Saudi Arabian hospital 15 , indicating the diversity of MRSA bearing PVL genes in the GCC countries. PVL gene-positive S. aureus have been associated with necrotic skin lesions and community-acquired necrotic pneumonia 24 .…”
Section: Discussioncontrasting
confidence: 72%
“…According to AlFouzan et al. [ 25 ], out of 291 S. aureus isolates, 30.6% were MRSA. Genes for PVL were detected in 14.6% and 12.0% of the MRSA and MSSA isolates, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Both MRSA types carried SCCmec type III, IV, IVc and V genetic elements. [ 25 ] In another meta-analysis including 76 studies from 31 countries, PVL strains were strongly associated with skin and soft-tissue infections, while comparatively rarely with pneumonia, musculoskeletal infections, bacteremias and colonizing strains. [ 26 ]…”
Section: Resultsmentioning
confidence: 99%
“…Many CA-MRSA strains carry PVL genes, whereas their frequency in MSSA and dominant HA-MRSA clones is much lower [15]. However, a few studies on PVL-positive MSSA have been published [154][155][156][157].…”
Section: Paper IImentioning
confidence: 99%